Quantitative and qualitative analyses of human salivary NEFA with gas-chromatography and mass spectrometry - Kulkarni, Bhushan V.; Wood, Karl V.; Mattes, Richard D. (Frontiers in Physiology, 2012)
Salivary NEFA are proposed to play a role in oral health, oral fat detection, and they may hold diagnostic and prognostic potential. Yet, little is known about the array and concentrations of NEFA in saliva. The aim of the study was to conduct qualitative and quantitative analysis of salivary NEFA in healthy humans and to present a new, efficient protocol to perform such analyses. Resting saliva samples from fifteen participants were collected. The salivary lipids were extracted using a modified Folch extraction. The NEFA in the extracted lipids were selectively subjected to pentafluorobenzyl bromide derivatization and qualitatively and quantitatively analyzed using Gas Chromatography-Mass Spectrometry. A total 16 NEFA were identified in resting saliva. The four major NEFA were palmitic, linoleic, oleic and stearic acids. Their concentrations ranged from 2-9 micromolar. This is the first study to characterize individual human salivary NEFA and their respective concentrations. The method used in the study is sensitive, precise, and accurate. It is specific to fatty acids in non-esterified form and hence enables analysis of NEFA without their separation from other lipid classes. Thus, it saves time, reagents and prevents loss of sample. These properties make it suitable for large scale analysis of salivary NEFA.